Ex 12.2, 1 Factorise the following expressions. (viii) 𝑎^4 + 2𝑎^2 𝑏^2 + 𝑏^4𝑎^4 + 2𝑎^2 𝑏^2 + 𝑏^4 Using (𝑎^𝑚 )^𝑛=𝑎^(𝑚 × 𝑛) ∴ (𝑎^2 )^2 = 𝑎^(2 × 2)=𝑎^4 = (𝑎^2 )^2+〖2𝑎〗^2 𝑏^2+(𝑏^2 )^2 = (𝒂^𝟐 )^𝟐+𝟐(𝒂^𝟐×𝒃^𝟐)+(𝒃^𝟐 )^𝟐 =(𝑎^2 )^2+(𝑏^2 )^2+2(𝑎^2×𝑏^2) Using (𝒙+𝒚)^𝟐=𝑥^2+𝑦^2+2𝑥𝑦 Here, 𝑥 = 𝑎^2 and y = 𝑏^2 = (𝒂^𝟐+𝒃^𝟐 )^𝟐

Go Ad-free
Davneet Singh's photo - Co-founder, Teachoo

Made by

Davneet Singh

Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 14 years. He provides courses for Maths, Science, Social Science, Physics, Chemistry, Computer Science at Teachoo.